(untitled) (Journal of Fiber Bioengineering and Informatics, 2020)
A novel model of heat and moisture transfer in human-chemical protective clothing-environment is proposed to predict the human physiological regulatory response wearing chemical protective clothing (CPC). The human thermal model is developed by dividing the skin node into multiple segments based on the Gagge's 2 node model. The CPC is discretized into multiple control volumes and the control volume-time domain finite difference method is utilized to compute the temperature of the clothing. The CFD simulation method is employed to calculate the heat and moisture transfer of natural convection in the air gap between human and CPC. The air gap model is coupled with the human model and the CPC model by exchanging boundary conditions. The predictions of human heat stress obtained by the model agree well with the published experimental data. The results indicate that the condensation heat transfer mechanism in CPC changes with the thickness of air gap. When the thickness of the air gap is small, the condensation heat transfer is mainly based on diffusion. When the air gap is thicker, the condensation heat transfer is dominated by the `heat pipe effect'. Compared with large changes in ambient temperature, the impact of ambient temperature on human temperature is not very great due to good air tightness and large thermal resistance of CPC, but that on sweating rate, moisture accumulated on the skin and moisture run off from the skin is great. Finally, based on the analysis of the results, the guidelines for the design of CPC are given.